Iklan Film dan Perubahan Kehidupan Sosial-Ekonomi Perkotaan 1950-1966 - Indira Ardanareswari (Lembaran Sejarah, 2012)
This paper deals with the roles of flm advertisements in the changes in lifestyle during the socalled Guided Democracy era in Indonesia. The discussion starts from an analysis on the roles of language and visual symbols in the dynamic changes of the society. Articles from newspapers and flm magazines issued in the period under study provide valuable data about the researched topic. It can be concluded that (1) the languages and the illustrations of flm advertisements changed along the changes of the society, (2) the commercialization of flm advertisements stimulated an increase in the consumption behavior of entertainment goods, and (3) there was an increasing public awareness to keep these changes under social controls.